Criticism of Positivism and Its Relevance to Az-Zahabi's Criticism of Ibn 'Arabi's Interpretation - Asnadi, Asnadi; Putra, Aldomi (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
Since the 19th century, positivism has prevailed in modern science via empirical observation, sensory verification, and objective reason. Although it has propelled advancements in science and technology, positivism fosters reductionism, thereby marginalizing unquantifiable entities, including spiritual and metaphysical realities. This constraint is particularly manifest in Islamic studies, notably in Sufi exegesis of the Qur'an, which depends on symbolism, inner signs, and spiritual experiences. Ibn ‘Arabi, a distinguished Sufi philosopher, offers speculative and figurative exegeses in texts such as al-Futūḥāt al-Makkiyyah and Fuṣūṣ al-Ḥikam, sometimes criticised for straying from literal orthodoxy. Az-Zahabi, a distinguished hadith scholar, denounced these interpretations as perilous, emphasising textual integrity and rational criteria over spiritual insights. These discussions highlight epistemological challenges between empirical rigor and transcendent sources of knowledge. This study uses a qualitative library research methodology to epistemologically examine Az-Zahabi’s critique of Ibn ‘Arabi’s interpretations of the Qur’an. An interdisciplinary approach integrates the philosophy of science with Qur’anic exegesis. Primary sources encompass Az-Zahabi’s Siyar Aʿlām al-Nubalā’ and Mizān al-Iʿtidal, in addition to the principal works of Ibn ‘Arabi. Secondary sources offer theoretical and contextual assistance. Data analysis employs descriptive and interpretive methodologies, including literature reviews, textual analyses to reveal interpretive assumptions, epistemological evaluations, and comparative syntheses. The findings demonstrate the insufficiency of positivism for esoteric religious knowledge, mirroring Az-Zahabi's argument centered on orthodoxy. Ibn ‘Arabi’s approach prioritises spiritual realisation above empirical constraints, facilitating a more profound understanding of texts. Critiquing positivism fosters an awareness of multiple Islamic epistemologies and methodological diversity, facilitating a comprehensive study of sacred texts.